The Use of H5P in Islamic Religious Education Learning Media Development to Improving Self-Regulated Learning - Angga Setiawan; Dzulfikar Akbar Romadlon (LP. Ma'arif Janggan Magetan, 2024)
The problem of teaching and learning activities in schools is something that is often found by teachers when teaching. One of them is the lack of learning independence in students, the criteria for learning independence itself is that students can be said to learn independently if these students are active, creative, disciplined and responsible. Learning media is a solution to support the realization of learning independence in students. One of them is H5P learning media which is expected to realize and increase learning independence in students. This study uses the Kemmis-McTaggart model Class Action Research method which is divided into 2 cycles, cycle I and cycle II through 4 stages of research for each cycle, namely: planning, acting, observation and reflection. The results of this study can be concluded that teaching and learning activities using H5P learning media can increase students' learning independence. This can be seen from the increase in students' learning independence from cycle I to cycle II.